Persepsi dan pengetahuan ibu terhadap pangan fungsional di Indonesia - Rosyida Nur Bayti Khusna; Lily Arsanti Lestari; Supriyati Supriyati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2023)
Mother’s perception and knowledge of functional food in IndonesiaBackground: Non-communicable diseases (NCD) is the highest cause of death in the world. At the end of 2019, the COVID-19 virus (Coronavirus disease) emerged and became a pandemic in various countries. Consumption of functional food is believed to become an alternative therapy for NCD and increase immunity amid the pandemic. A mother's perception of purchasing functional food is essential because of its main role as a food provider in the family. Objective: This research was conducted to determine the factors related to the mother's purchase of functional food. Methods: An online cross-sectional survey was carried out among 406 mothers and distributed through the social media platform for two weeks from November to December 2021. Each subject answered questions on general data, basic knowledge, motivation, and buying patterns of functional food products, and ten questions about the perception of functional food. The questionnaires were tested for validity and reliability before being distributed. Data were processed using univariate and bivariate analysis using the Pearson correlation test with STATA software version 15.0.Results: 55.91% of mothers have an excellent knowledge of functional food. Purchasing functional food was not significantly related to socio-demographic (age, occupation, and education) with p-value>0.05 (0,9088; 0,4413; 0,7451) but significantly associated with knowledge (p-value=0.0161) and behavior which analyzed using the theory of planned behavior including attitudes, subjective norms, and perceived behavioral controls (p<0.05). Mothers purchase functional food products mainly because of health and taste reasons. At the same time, the barriers are due to high prices and lack of information regarding the health benefits contained. Conclusion: Mother's purchasing behavior is not influenced by socio-demographic conditions because they already have a good awareness of functional food. Mother's knowledge and behavior toward functional food are good because of their high educational level, and healthy food awareness increased during the pandemic. Intensive education and product innovation are still needed to support functional food development in Indonesia.